1997
DOI: 10.1590/s0103-06631997000400002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Characteristics of Supernumerary Teeth in Brazilian Children: Consequences and Proposed Treatments

Abstract: The study had the objective of identifying the frequency of supernumerary teeth on patients attended at the Pediatric Dentistry Clinic at the School of Dentistry of the Universidade Federal do Rio de Janeiro (FO-UFRJ), from 1981 to 1990, relating the frequency to the sex and dentition of the patients. Some characteristics relating to and consequential upon the pathology, as well as the proposed treatments, are also part of this work. To achieve the proposed objectives, 1,907 files of patients with full mouth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 2 publications
3
28
1
5
Order By: Relevance
“…In accordance with most studies (3,(15)(16)(17)(18)26,27), we observed that 92% of the ST were located in the maxilla, and this percentage was very close to that reported by De Oliveira Gomes et al (5), that is, 91.3%. It has been reported in our study in accordance with the other studies that the most commonly diagnosed ST were mesiodens (3,5,(15)(16)(17)26).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with most studies (3,(15)(16)(17)(18)26,27), we observed that 92% of the ST were located in the maxilla, and this percentage was very close to that reported by De Oliveira Gomes et al (5), that is, 91.3%. It has been reported in our study in accordance with the other studies that the most commonly diagnosed ST were mesiodens (3,5,(15)(16)(17)26).…”
Section: Discussionsupporting
confidence: 92%
“…The reported prevalence of ST in various populations ranges from 0.1% to 3.8% (3)(4)(5)8,(12)(13)(14)(15)(16)(17)(18)(19). The prevalence has been estimated to be 1.05% in Spanish (20), 1.53% in Hungarian (13), 2.1% in British (19), 2.7% in Chinese (14), 2.96% in Brazilian (18), and 3.2% in Mexican (15) populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valores similares fueron reportados por Buenviaje & Rapp (1984) con 0,5% en americanos, por Fernández Montenegro et al (2006) con 0,4% en españoles, por AltugAtac & Erdem (2007) con 0,4% en turcos y por Harris & Clark (2008) con 0,6% en americanos caucásicos. En brasileños la prevalencia varió entre 1,4 y 3,7% (Primo et al,1997;Coutinho et al;Leite Segundo et al, 2006); en turcos varió entre 0,4 y 2,7% (Altug-Atac & Erdem; Esenlik et al;Celikoglu et al,2010); en españoles varió entre 0,4 y 3,2% (Salcido-García et al, 2004;Fernández Montenegro et al;Leco Berrocal et al); en suecos no hubo variación expresiva, estando entre 1,1 y 1,9% (Thilander & Myberg, 1973;Bergstrom, 1977;Bäckman & Wahlin, 2001); en chinos se han encontrado en 2,7% (Davis, 1987;King et al, 2010); en griegos 1,8% (Fardi et al, 2011); en niños daneses entre 9 y 10 años (Locht et al, 1980); en australianos 1,8% (Thongudomporn & Freer, 1998). Valores expresivos como 6 % fueron publicados por Harris & Clark en americanos melanodermas.…”
Section: Resultsunclassified
“…Los DS pueden ocurrir tanto en la maxila como en la mandíbula, sin embargo, son más frecuentes en la maxila, representando 67 a 96% de los casos (Danalli et al, 1988;Primo et al;Alaejos et al, 2000;Rajab & Hamdan;SalcidoGarcía et al;Fernández-Montenegro et al;Leco Berrocal et al;Esenlik et al;Celikoglu et al;Vahid-Dastjerdi et al, 2011).…”
Section: Resultsunclassified